2012
DOI: 10.2466/02.07.09.pr0.110.2.469-474
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Self-Esteem, Stress, and Physical Activity in College Students

Abstract: The purpose of this study was to identify population and sex-specific relationships between perceived stress, self-esteem, and physical activity in college students. 90 students, ages 18 and older and enrolled in five sections of a health and human behavior class during the spring 2010 semester, were contacted for this study with 74 consenting to serve as study participants. Each participant completed three surveys: the Rosenberg Self-Esteem Scale, the Perceived Stress Scale, and the International Physical Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 13 publications
(16 reference statements)
3
17
2
4
Order By: Relevance
“…However, the lack of correlation between BES, SES and training variables appears to be consistent with the results presented by A. Hubbs et al (2012). Moreover, it is also suggested that this problem should be considered in the aspects of training motives, as well as its effectiveness in terms of achieving success in sports.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the lack of correlation between BES, SES and training variables appears to be consistent with the results presented by A. Hubbs et al (2012). Moreover, it is also suggested that this problem should be considered in the aspects of training motives, as well as its effectiveness in terms of achieving success in sports.…”
Section: Discussionsupporting
confidence: 86%
“…Self -esteem is considered as a primary element of welfare (Rosenberg, 1965). Majority of researchers (McAuley et al, 2005;Griffin, Kirby, 2007), despite the complexity of the problem (Hubbs, Doyle, Bowden, Doyle, 2012;Ziemianek, Jendrysik, Horodecki, Knapik, 2015), consider physical activity as beneficial for self -esteem. Analysis of average values and median of SES of the respondents (Table 1) may lead to conclusion that mutual relations between activities and SES are generally favourable.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in two cross-lagged studies, exercise at time 1 did not predict stress at time 2 [20, 110]. Furthermore, several studies have found no relationship between stress and exercise constructs [111, 112] or relationships that were positive instead of negative [113, 114]. …”
Section: Introductionmentioning
confidence: 99%
“…Students with poor mental health may hook up in order to cope with negative emotions, poor self-image (Kenney et al, 2014) or other reasons that heighten the risk of experiencing negative consequences. Mental distress is associated with poor decision-making skills (see Castaneda, Tuulio-Henriksson, Marttunen, Suvisaari, & Lönnqvist, 2008 for review), low self-esteem (Hubbs, Doyle, Bowden, & Doyle, 2012; Merianos, Nabors, Vidourek, & King, 2013), and a lack of perceived social support (Ruthig, Haynes, Stupnisky, & Perry, 2009). In turn, negative hookup experiences may further exacerbate distress and lead to more risky hookup behaviors.…”
Section: Discussionmentioning
confidence: 99%